Regime Change and Fight Against Corruption in Nigeria: A Focus on President Buhari’s Democratic Administration - Ogbe, Henry Ejotubu; Ejovi, Austin (Social Science Research, 2022)
The high numbers of cases of corruption in Nigeria have caused many Nigerians to bother and think about the way out of the problem. The study focused on regime change towards the fight against corruption in Nigeria with emphasis on President Muhammadu Buhari democratic government, particularly his first tenure. The study utilized secondary data, as well as conceptualized the fight against corruption as a conceptual framework for the study. The study re-emphasized: that President Buhari perceived corruption as the greatest form of human rights violation; that Nigeria ecosystem breeds corruption owing to the existence of impunity emanating from lack of independence of the institutions and other agencies handling anti-corruption matters; that President Buhari’s bravery to fight against corruption no matter whose ox is gore served as a red flag to bureaucratic corruption in Nigeria despite the perception of some persons that anti-corruption fight of the president is selective; that Buhari bravery to fight against corruption was boosted by his political party (APC) constitution item No 4 which clearly states the party’s position against corruption. The study recommended among others that law should be enacted to mandate all political parties in Nigeria to have anti-corruption law in their constitutions and the adoption of equality before the law in handling corruption cases by the anti-corruption institutions, and the law courts.